Effects of conservative versus liberal oxygen treatment in mortality of UCI patients - da Rocha Simões, Carolina; Accoce, Matías (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Background: The oxygen is a drug that is commonly used in clinical practice and whose therapeutic use has been adjusted over time. However, this practice confronts us with one of the transcendental problems, which is the inconsistency of the optimal oxygen level established in the clinical practice guidelines. Currently the treatment is liberal and leads to abnormally high levels of oxygen causing damage locally and systemically. The consequence of this is increased mortality in patients who are treated with high levels of oxygen. In view of this, conservative therapy was proposed to avoid hyperoxemia and mitigate its adverse effects. The optimal level of oxygen for the treatment of patients admitted to the intensive care unit remains uncertain. Material and methods: A comprehensive electronic search of the relevant literature on conservative and liberal treatment in intensive care unit inpatients was performed through medical databases as well as reference search engines such as Pubmed, Cochrane, trip, epistemonikos, Australian New Zealand clinical trial registry and clinicaltrial.gov. For this, the following keywords and MESH terms were used: “conservative oxygen therapy”, “conservative oxygen therapy and mortality”, “conservative oxygen therapy and critical care”, “conservative oxygen therapy and critically ill”. Randomized clinical trials, systematic reviews, and meta-analyses were identified without considering publication status, reported results, date or year of publication, and language. Results: Were included 21 systematic review and meta-analysis papers that compared liberal with conservative treatment and were within the inclusion criteria and 13 randomized clinical trials. Conclusion: Currently, the available evidence on targeted oxygen therapy in intensive care patients remains inconclusive. More randomized clinical trials are needed to determine the ideal oxygen target for intensive care patients and its impact on mortality)